Slow geminate-charge-pair recombination dynamics at polymer: Fullerene heterojunctions in efficient organic solar cells - Provencher, Françoise; Sakowicz, Maciej; Brosseau, Colin-Nadeau; Latini, Gianluca; Beaupré, Serge; Leclerc, Mario; Reynolds, Luke X.; Haque, Saif A.; Leonelli, Richard; Silva, Carlos (Journal of polymer science. Part B, Polymer physics, 2012)
We explore charge recombination dynamics at electron donor‐acceptor heterojunctions, formed between a semiconductor polymer (PCDTBT) and a fullerene derivative (PC70BM), by means of combined time‐resolved photoluminescence and transient absorption spectroscopies. Following prompt exciton dissociation across the heterojunction, a subset of bound electron‐hole pairs recombines with a temperature‐independent rate distribution spanning submicrosecond timescales to produce luminescent charge‐transfer excitons (CTX). At 14 K, this slow mechanism is the dominant geminate charge recombination pathway, whereas we also observe CTX emission on subnanosecond timescales at 293 K. We thus find that at these temperatures, a fraction of the initial charge‐pair population is trapped deeply such that they only recombine slowly over a broad distribution of timescales by quantum tunneling. We identify geminate polaron pairs (GPP) as a reservoir of long‐lived localized states that repopulate the CTX up to microsecond timescales. The observation of such distributed geminate‐charge recombination highlights the importance of the molecular nature of specific donor–acceptor electronic interactions in defining the relaxation pathways of trapped GPP. © 2012 Wiley Periodicals, Inc. J Polym Sci Part B: Polym Phys, 2012 Charge‐transfer‐exciton recombination dynamics are probed over timescales orders of magnitude longer than has been previously reported for PCDTBT:PC70BM donor‐acceptor heterostructures. Delayed photoluminescence is attributed to slow generation of charge‐transfer excitons via tunneling from deeply trapped geminate polaron pairs. Using time‐resolved spectroscopic measurements at various temperatures and photophysical modeling, it is estimated that 16% of geminate recombination at room temperature originate from this slow mechanism.